Urinary bladder cancer risk factors in an area of former coal, iron, and steel industries in Germany. Issue 7 (18th April 2017) - Krech, Eugen; Selinski, Silvia; Blaszkewicz, Meinolf; Bürger, Hannah; Kadhum, Thura; Hengstler, Jan G.; Truss, Michael C.; Golka, Klaus
ABSTRACT: This study was performed to investigate the frequency of bladder cancer in patients with an occupational history such as underground hard coal mining and/or painting after the structural change in the local industry. A total of 206 patients with bladder cancer and 207 controls were enlisted regarding occupational and nonoccupational bladder cancer risk factors by questionnaire. The phase II enzymes N -acetyltransferase 2 (NAT2), glutathione S -transferases M1 (GSTM1), and T1 (GSTT1) and the single nucleotide polymorphism (SNP) rs11892031[A/C] reported to be associated with bladder cancer in genome-wide association studies were genotyped. The bladder cancer risk in varnishers and underground hard coal miners was increased as previously shown in a study in this area performed in the 1980s. The occupation of a car mechanic was associated with a significantly elevated bladder cancer risk and higher in the case of underground hard coal miners even though the mine was closed in 1987. The frequency of GSTM1 negative genotype was comparable in cases and controls (53% versus 54%). In the case of NAT2, the slow NAT2 genotype was more frequent (62% versus 58%) and ultra-slow NAT2 genotype (NAT2*6A and/or *7B alleles only) was 23% versus 15%. An occupational history of a varnisher or an underground hard coal miner remains a risk factor for bladder cancer occurrence. Data indicate that in the case of bladder cancer, GSTM1 is a susceptibility factor related to environmental and/or occupational exposure.